2017
DOI: 10.1002/anie.201700814
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Rationally Halogenated Buckybowls by Chemoselective Aromatic C−F Bond Activation

Abstract: Halogenated buckybowls or bowl-shaped polycyclic aromatic hydrocarbons (BS-PAHs) are key building blocks for the "bottom-up" synthesis of various carbon-based nanomaterials with outstanding potential in different fields of technology. The current state of the art provides quite a limited number of synthetic pathways to BS-PAHs; moreover, none of these approaches show high selectivity and tolerance of functional groups. Herein we demonstrate an effective route to BS-PAHs that includes directed intramolecular ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 51 publications
0
42
0
4
Order By: Relevance
“…[14,15] Following this strategy, we were able to construct various polycyclic aromatic hydrocarbons (PAH) with near-quantitative yields. [14][15][16] Recently we have demonstrated that the C─F bond activation by aluminum oxide allows performing effective coupling in truly domino-like manner ( Figure 1). [17] The high efficiency and the possibility to perform the final transformation in solid state makes this approach highly attractive for the synthesis of virtually insoluble NGs.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Following this strategy, we were able to construct various polycyclic aromatic hydrocarbons (PAH) with near-quantitative yields. [14][15][16] Recently we have demonstrated that the C─F bond activation by aluminum oxide allows performing effective coupling in truly domino-like manner ( Figure 1). [17] The high efficiency and the possibility to perform the final transformation in solid state makes this approach highly attractive for the synthesis of virtually insoluble NGs.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly fueled by the demand from physicist chasing for the unique PAHs’ properties such as charge carrier mobilities, singlet fission, and many others . Naturally, family of PAHs consists of numerous subclasses, among which non‐planar PAHs bearing bowl‐shaped geometry exhibit highly interesting features, which cannot be properly investigated due to drastic lack of the synthetic approaches toward the so‐called buckybowls . The explanation for such a scarcity of methodologies in the seemingly well‐established field is mainly connected to the strain energies that originate from the valence angles’ deviations, resulting in non‐planar structures resembling a bowl.…”
Section: Introductionmentioning
confidence: 99%
“…Althought he first two methods face both low group tolerance and moderate yields, the last one often possess highs electivity and frequentlyl eads to nearly quantitative yields showingt olerance to variousf unctional groups. [15,16] Diindeno [1,2,3,4-…”
mentioning
confidence: 99%